Distinct cellulose and callose accumulation for enhanced bioethanol production and biotic stress resistance in OsSUS3 transgenic rice. (15th March 2020) - Fan, Chunfen; Wang, Guangya; Wu, Leiming; Liu, Peng; Huang, Jiangfeng; Jin, Xiaohuan; Zhang, Guifeng; He, Yueping; Peng, Liangcai; Luo, Keming; Feng, Shengqiu
Highlights: The wall polysaccharides levels and features were altered in OsSUS3 transgenic plants. Biomass saccharification and bioethanol yield were enhanced in OsSUS3 plants. Rapid callose deposition improved resistances to multiple biotic stresses. Dynamic carbon partitioning regulated wall polysaccharide biosynthesis. Abstract: Genetic modification of plant cell walls is an effective approach to reduce lignocellulose recalcitrance in biofuel production, but it may affect plant stress response. Hence, it remains a challenge to reduce biomass recalcitrance and simultaneously enhance stress resistance. In this study, the OsSUS3- transgenic plants exhibited increased cell wall polysaccharides deposition and reduced cellulose crystallinity and xylose/arabinose proportion of hemicellulose, resulting in largely enhanced biomass saccharification and bioethanol production. Additionally, strengthening of the cell wall also contributed to plant biotic resistance. Notably, the transgenic plants increased stress-induced callose accumulation, and promoted the activation of innate immunity, leading to greatly improved multiple resistances to the most destructive diseases and a major pest. Hence, this study demonstrates a significant improvement both in bioethanol production and biotic stress resistance by regulating dynamic carbon partitioning for cellulose and callose biosynthesis in OsSUS3- transgenic plants. Meanwhile, it also provides a potential strategy for plant cell wall modification.